2008
DOI: 10.1083/jcb.200710050
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Dvl, c-Jun, β-catenin, and TCF form a complex leading to stabiLization of β-catenin–TCF interaction

Abstract: In canonical Wnt signaling, Dishevelled (Dvl) is a critical cytoplasmic regulator that releases β-catenin from degradation. Here, we find that Dvl and c-Jun form a complex with β-catenin–T-cell factor 4 (TCF-4) on the promoter of Wnt target genes and regulate gene transcription. The complex forms via two interactions of nuclear Dvl with c-Jun and β-catenin, respectively, both of which bind to TCF. Disrupting the interaction of Dvl with either c-Jun or β-catenin suppresses canonical Wnt signaling–stimulated tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
237
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(255 citation statements)
references
References 48 publications
17
237
1
Order By: Relevance
“…Itoh et al showed notably that the nuclear localization of Xenopus Dvl is essential for its ability to stabilize b-catenin (Itoh et al, 2005;Gan et al, 2008). Here, we observe the colocalization of WWOX with Dvl-2 wild type or Dvl2NESm (a mutated form of Dvl-2 predominantly localized in the nucleus) in the cytoplasmic compartment (Figure 8).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Itoh et al showed notably that the nuclear localization of Xenopus Dvl is essential for its ability to stabilize b-catenin (Itoh et al, 2005;Gan et al, 2008). Here, we observe the colocalization of WWOX with Dvl-2 wild type or Dvl2NESm (a mutated form of Dvl-2 predominantly localized in the nucleus) in the cytoplasmic compartment (Figure 8).…”
Section: Discussionsupporting
confidence: 61%
“…Recently, it has been shown that Dvl proteins shuttle between the cytoplasm and the nucleus, and that their nuclear localizations are crucial for their functions in the Wnt/b-catenin pathway (Itoh et al, 2005;Yokoyama and Yin DMalbon 2007;Gan et al, 2008). Itoh et al showed notably that the nuclear localization of Xenopus Dvl is essential for its ability to stabilize b-catenin (Itoh et al, 2005;Gan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we found that the induction of Snail expression by decreasing AF6 expression was mediated primarily via Dvl2. Emerging work suggests that Dvl2 plays an important role in the nuclear regulation of gene expression [38][39][40] . Further analysis identified FOXE1, a transcription factor, as a binding partner of AF6.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, β-catenin is stabilized and accumulates in the nucleus to activate TCF/ LEF-1 target genes. Recent studies have unraveled that Dvl also functions in the nucleus [6], through stabilizing β-catenin/TCF interaction by forming a quaternary complex consisting of Dvl, c-Jun, β-catenin and TCF [7]. In addition to regulating the canonical Wnt signaling, Dvl has also been suggested to be an essential transducer in non-canonical Wnt signaling pathways [8,9].…”
Section: Introductionmentioning
confidence: 99%